When green carbon plants meet synthetic biology - Qing Wang; Jianfeng Zhang; Qiulan Dai; Meijie Cui; Hao Yang; Peijian Cao; Lei Zhao (Modern Agriculture)
Abstract Recycling carbon dioxide (CO2) into chemicals or fuels presents a promising avenue for mitigating carbon emissions and addressing the energy crisis. Plants serve as the ideal platform for the production of materials and chemicals, thanks to their innate capacity to directly use CO2 in the synthesis of various organic compounds. While conventional methods for enhancing plant CO2 fixation may reach their limits, novel technological solutions are imperative. Synthetic biology has illuminated the potential for biosynthesising multiple carbon sources through artificial CO2 fixation pathways in vitro. Recent breakthroughs in photorespiratory bypasses and artificial carboxylation modules offer significant promise for engineering plants to improve carbon fixation, guiding the design and development of plants with more efficient CO2 utilisation. In this context, we begin by summarising recent progress in designing or engineering in vitro CO2 fixation pathways, as well as those solely established in microbes. Subsequently, we delineate strategies employed to enhance CO2 fixation in plants. Finally, we explore potential methods for introducing artificial CO2 fixation pathways into plants. These advancements are critical in advancing synthetic biology's efforts to tackle future challenges related to food and energy scarcity.